Serving rural low‐income markets through a social entrepreneurship approach: Venture creation and growth - Prado, Andrea M.; Robinson, Jeffrey A.; Shapira, Zur (Strategic Entrepreneurship Journal, 2022)
Abstract Research Summary Rural communities in developing countries often exhibit high poverty levels, lack of skilled labor, and limited infrastructure. Through an analysis of three social ventures serving rural low‐income markets in Latin America, we explore how social entrepreneurs create and grow their ventures. We advance a multilevel framework that incorporates three main levels within the creation and growth process of social ventures serving these markets. At the individual level, founders are continuously revising goals and acquiring new capabilities. At the community‐relations level, they engage in explicit efforts to ground business operations in the community. At the organizational level, they pursue innovative business models. These processes are dynamic and interdependent. This framework contributes to the research on social venture creation and growth in uncertain and resource‐constrained environments. Managerial Summary Philanthropy or base of the pyramid (BoP) initiatives by multinational corporations have sought to alleviate poverty in rural low‐income communities in developing countries. Social entrepreneurship constitutes an alternative mechanism to generate social impact by bringing products and services to this market segment in a financially sustainable way. However, the creation and growth of a social venture in this context pose multiple challenges given the socioeconomic conditions of its populations and the limited access to public infrastructure. Based on a comparative analysis of three Latin American enterprises, our research suggests the following takeaways for social entrepreneurs seeking to serve these communities: (a) be willing to change goals and acquire new capabilities (e.g., business training); (b) see the community not only as customers or beneficiaries but also as a source of useful resources to deploy in the venture's operation; and (c) innovate in business model components (e.g., distribution, marketing, human resource management) that, due to limiting conditions in these communities, require a different approach than in mainstream markets.